The Devil's Own: A Romance of the Black Hawk War - Parrish, Randall, 1858-1923; Kinney, Margaret West, 1872-1952; Kinney, Troy, 1871-1938 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Devil's Own: A Romance of the Black Hawk War" by Randall Parrish is a historical novel written in the early 20th century. Set against the backdrop of the Black Hawk War of 1832, it explores themes of conflict, identity, and romance. The narrative appears to follow the experiences of a young army officer, Lieutenant Knox, as he navigates both the tensions of frontier life and the complexities of human relationships during a time of strife. The opening of the book introduces us to Lieutenant Knox stationed at Old Fort Armstrong, where he reflects on the growing unrest with the Native American tribes, particularly Black Hawk and his warriors. As he observes the landscape and the activities around him, Knox discusses the precarious situation with a fellow officer, revealing the fragile peace and the looming threat of violence. The introduction of characters such as Judge Beaucaire and the gambler Joe Kirby further sets the stage for a tale intertwining personal stakes with historical events. This portion lays the groundwork for an engaging narrative that promises not only action and adventure but also examines the human dramas that unfold amidst the chaos of war. (This is an automatically generated summary.)
Release date is 2006-02-07
E-text prepared by Al Haines
Keywords: Black Hawk War, 1832 -- Fiction